From Pacing to Rapport: Building Communication with Generation Z in Smart City Laboratory - Suprijandoko, Firman (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2024)
This research is part of a series of studies under the broad theme of